Effectiveness of Surgical Treatment in Carpal Tunnel Syndrome Mini-Incision Using MIS-CTS Kits: A Cadaveric Study - Wongthawat Liawrungrueang; Sunton Wongsiri (Advances in Orthopedics)
Introduction. Carpal tunnel syndrome (CTS) is caused by the compression of the median nerves in the wrist. Patients have pain and numbness in the hands. According to the records of Songklanagarind Hospital from 2015 to 2018, of 800 patients, 196 or 24.5% were treated with surgery. The novel tool of minimally invasive surgery for carpal tunnel syndrome (MIS-CTS) was developed to improve effectiveness and safety. Purpose. This study was performed to the effectiveness of visualization during surgery and the complete release of the transverse carpal ligament (TCL) and also the safety of using the MIS-CTS kits. Methods. Twenty fresh cadaveric forearms had surgery. Surgical techniques were (1) incision 15–18 mm at palmar hand; (2) the scissors and the navigator were inserted to create working space underneath the palmar aponeurosis; (3) the visual enhancer was inserted. The visual enhancer improves the visual field by shielding the soft tissue around the operative field; (4) the TCL was cut at the distal TCL by surgery scalpel, and then a flexible freer was used to detach the fibrous tissue from the median nerve and the TCL; and (5) the TCL cutting blade was pushed straight to cut the TCL completely from distal to proximal. TCL length was observed until the complete release. The median nerve and the recurrent branch of the median nerve were observed. Results. All TCL were cut completely. All median nerves, recurrent branches of the median nerve, and superficial palmar arches could be observed during the operation, and none were injured. This technique showed effectiveness and safety for minimally invasive carpal tunnel surgery. Conclusions. The study found that the new device, MIS-CTS kits, along with this technique is effective for CTS release in terms of minimally invasive open carpal tunnel surgery.